STEM Learning: The Way to Construct Undergraduate Students’ Oral Communications Skills in Science Learning - Nurramadhani, Annisa; Riandi, Riandi; Permanasari, Anna; Suwarma, Irma Rahma (IJIS Edu : Indonesian Journal of Integrated Science Education, 2023)
Communication skills are one of the skills that a person must have when entering the world of work. Theworkforce in a company that lacks mastering 21st century skills will be at a disadvantage to compete globally,and will have difficulty in dealing with challenges that arise along with the with the development of scienceand technology. So, in higher education such as university, the curriculum, course, and learning shouldprovide the activities that could improve and construct students’ communications skills. STEM is one ofthe learning approaches that could help to construct students’ communication skills. Research objective isto investigate how is the development of oral science communications skills of undergraduate students inEnvironmental learning by using STEM learning approaches. The method of this research is qualitativeresearch by the data taken from observation and teaching learning video recording transcriptions. Thetranscription is coded by the assessment of science communication rubrics adapted from BaltimoreUniversity for oral science communication. The data are taken from students’ presentation activities inenvironmental courses. This research result shows that responsiveness indicators is 88,3%, multimediasupported as technology skills is 83,3%, and conclusions indicators is 50,0%. It could be concluded thatSTEM learning approaches could be constructed students’ oral communications skills. Responsiveness andmultimedia support of oral communications skills indicators are outperformed than conclusion as the leastperformed of oral communications skills.